1995
DOI: 10.1002/j.1460-2075.1995.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Unique features of internal initiation of hepatitis C virus RNA translation.

Abstract: The question of whether hepatitis C virus (HCV) RNA is translated by a mechanism of internal ribosome entry has been examined by testing whether insertion of HCV sequences between the two cistrons of a dicistronic mRNA promotes translation of the downstream cistron in rabbit reticulocyte lysates. Deletion analysis showed that efficient internal initiation required a segment of the HCV genome extending from about nucleotides 40–370 and that deletions from the 3′‐end of this element were highly deleterious. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
310
3
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(332 citation statements)
references
References 42 publications
14
310
3
1
Order By: Relevance
“…The role of aCP-2 in translational enhancement may be shared by other picornaviruses+ Cap-independent translation initiation within the picornavirus family is mediated by two major classes of IRESs (type I and type II)+ These IRESs differ in their sequences, secondary structures, and biological properties (Wimmer et al+, 1993;Ehrenfeld, 1996)+ The enteroviruses and rhinoviruses utilize type I IRESs, and the cardioviruses and aphthoviruses utilize the type II IRES elements+ Although aCP-2 is capable of interacting in vitro with both type I IRESs (from coxsackievirus strain B and human rhinovirus) and type II IRES (from encephalomyocarditis virus and foot-and-mouth disease virus), an effect on translation of the cardiovirus and aphthovirus has not been demonstrated+ These data suggest that a functional role for aCP-2 in binding to viral 59 UTRs appears to be limited to type I IRES elements (Walter et al+, 1999)+ aCP plays a role in the translation of viruses in addition to those in the picornavirus family+ Although the IRES element of hepatitis A virus (HAV) cannot easily be classified as a type I or type II IRES (Brown et al+, 1994), aCP-2 is required to facilitate HAV internal ribosome entry similarly to type I IRESs (Graff et al+, 1998)+ Along the same lines, the hepatitis C virus (HCV) IRES has been difficult to classify as a type I or type II IRES due to its unique structure (Reynolds et al+, 1995)+ Whereas aCP-1 and aCP-2 can bind specifically to the HCV 59 UTR (Spangberg & Schwartz, 1999), it has not been possible to document an effect of this binding on HCV translation (Fukushi et al+, 2001)+ In this respect, the HAV IRES behaves in a manner reminiscent of a type I IRES, whereas HCV IRES resembles a type II IRES+ Thus, aCP binding can contribute to both silencing and enhancement of translation+ The former action is mediated by 39 UTR complexes and the latter by complexes within the 59 IRES segments of picornaviruses+ In neither case are the downstream events that control the rates of ribosome loading clearly defined+ In both cases, the complexes are formed at substantial distances from the sites of translation initiation+ Whether the two processes converge on a common pathway remains an interesting possibility+ Delineation of the 274…”
Section: Translational Enhancementmentioning
confidence: 99%
“…The role of aCP-2 in translational enhancement may be shared by other picornaviruses+ Cap-independent translation initiation within the picornavirus family is mediated by two major classes of IRESs (type I and type II)+ These IRESs differ in their sequences, secondary structures, and biological properties (Wimmer et al+, 1993;Ehrenfeld, 1996)+ The enteroviruses and rhinoviruses utilize type I IRESs, and the cardioviruses and aphthoviruses utilize the type II IRES elements+ Although aCP-2 is capable of interacting in vitro with both type I IRESs (from coxsackievirus strain B and human rhinovirus) and type II IRES (from encephalomyocarditis virus and foot-and-mouth disease virus), an effect on translation of the cardiovirus and aphthovirus has not been demonstrated+ These data suggest that a functional role for aCP-2 in binding to viral 59 UTRs appears to be limited to type I IRES elements (Walter et al+, 1999)+ aCP plays a role in the translation of viruses in addition to those in the picornavirus family+ Although the IRES element of hepatitis A virus (HAV) cannot easily be classified as a type I or type II IRES (Brown et al+, 1994), aCP-2 is required to facilitate HAV internal ribosome entry similarly to type I IRESs (Graff et al+, 1998)+ Along the same lines, the hepatitis C virus (HCV) IRES has been difficult to classify as a type I or type II IRES due to its unique structure (Reynolds et al+, 1995)+ Whereas aCP-1 and aCP-2 can bind specifically to the HCV 59 UTR (Spangberg & Schwartz, 1999), it has not been possible to document an effect of this binding on HCV translation (Fukushi et al+, 2001)+ In this respect, the HAV IRES behaves in a manner reminiscent of a type I IRES, whereas HCV IRES resembles a type II IRES+ Thus, aCP binding can contribute to both silencing and enhancement of translation+ The former action is mediated by 39 UTR complexes and the latter by complexes within the 59 IRES segments of picornaviruses+ In neither case are the downstream events that control the rates of ribosome loading clearly defined+ In both cases, the complexes are formed at substantial distances from the sites of translation initiation+ Whether the two processes converge on a common pathway remains an interesting possibility+ Delineation of the 274…”
Section: Translational Enhancementmentioning
confidence: 99%
“…At the moment, we have no information about the molecular events that might lead to the initiation of ARFP synthesis; however, several possibilities can be considered+ For example, the AUG of the main ORF, or an up-stream AUG, could be the start site of translation, with the reading frame slipping forward to bypass the stop codon at bases 2-4 (in the ϩ1 reading frame)+ Frame shifts are known to occur during gene expression of many viruses (Brierley, 1995)+ Alternatively, translation of ARFP might involve a non-AUG initiator codon; in fact, the HCV IRES has the power to direct translation from codons other than AUG (Reynolds et al+, 1995)+ Moreover, a recent report indicates that a novel translation initiation mechanism can lead to the synthesis of out-of-frame peptides (even some without upstream AUG initiation codons), which are then expressed by MHC class I molecules and stimulate immune responses (Malarkannan et al+, 1999)+ This report describes a series of non-AUG codons that allow translation of out-of-frame peptides at levels that elicit robust T cell responses+ One of these unusual start codons is AUC+ This unusual start codon is the third in-frame codon in .90% of the ϩ1 alternate reading frames of the reported HCV sequences+ If this were the start codon for the ARFP, then the expected product would range from 122 to 158 amino acids in the majority of sequences+ Finally, RNA stuttering could modify the sequence of HCV RNA during RNA replication, generating a new RNA that has ARFP as its translation product+ Stuttering gives rise to the RNA sequences required for the expression of proteins in most members of the Paramyxoviridae family (Liston & Briedis, 1995)+ If stuttering occurs during HCV replication, it could lead to the expression of chimeric proteins with amino terminal portions of the HCV core protein linked to carboxy-terminal portions of ARFP+ HCV sequences that could give rise to such chimeric proteins have been detected in PCR products from hepatocellular carcinoma (Ruster et al+, 1996) and the ascitic fluid of a patient with hepatocellular carcinoma (Yeh et al+, 1997)+ Our studies do not indicate whether ARFP plays a role in the HCV life cycle, or is synthesized "fortuitously+" However, the ORF is present in all reported HCV genotypes, and all the infectious clones described to date+ If ARFP has an impact on cellular or viral function, its highly basic nature and lack of a known nuclear localization signal suggests an interaction with cytoplasmic RNA, perhaps HCV RNA itself+ A possible role of ARFP in cellular transformation must be considered in light of studies showing chimeric proteins containing portions of ARFP might be expressed in HCC tissue and ascitic fluid (Ruster et al+, 1996; Yeh et al+, 1997)+ ,0+025 a HCV (13/100) vs+ total non-HCV (3/104)…”
Section: Arfp Properties and Synthesismentioning
confidence: 99%
“…Hepatitis C virus (HCV), a plus sense RNA virus identified in 1989 (Choo et al+, 1989), is estimated to chronically infect roughly 4,000,000 people in the United States (National Institutes of Health, 1997), often with serious consequences (for a review, see Branch et al+, 2000)+ Because HCV poses a public health threat, it is important to identify all HCV RNA structural elements and expressed polypeptides to define all potential diagnostic markers, vaccine components, and targets for pharmaceutical agents+ At the moment, HCV RNA is known to contain a single large open reading frame (ORF), about 9,000 nt in length, encoding a single polyprotein that is the source of 10 viral proteins: the core, E1, E2, P7, NS2, NS3, NS4a, NS4b, NS5a, and NS5b (Rice, 1996)+ This ORF is flanked by about 350 nt at its 59 end and about 220 at its 39 end+ Although the full range of the functions provided by the flanking sequences is not yet clear, terminal structures are likely to play a role in replication, and the 59 flanking sequence forms part of an internal ribosome entry site (IRES) that promotes the initiation of HCV polyprotein synthesis (Brown et al+, 1992;Tsukiyama-Kohara et al+, 1992;Reynolds et al+, 1995;Lu & Wimmer, 1996)+ As exemplified by the hepatitis B virus, viral genomes often contain overlapping genes+ Thus, HCV RNA may contain regions where the main ORF is overlapped by another gene or by an RNA structural element+ To seek these multifunctional regions, we carried out comparative sequence analysis on diverse HCV sequences retrieved from GenBank (Benson et al+, 1996), locating synonymous codons in the standard HCV ORF in which the third position nucleotides are much more conserved than chance alone would pre-dict+ This unusual third-base conservation is likely to occur in regions that have novel functions in addition to their known coding function (see Materials and Methods)+ Previous studies identified some of the regions of HCV RNA that have unusual nucleotide conservation (Ina et al+, 1994;Smith & Simmonds, 1997) and, in particular, they revealed that the RNA sequence of the core-encoding region is more conserved than would be necessary to maintain the observed level of conservation of the core protein+ Ina and colleagues (Ina et al+, 1994) suggested that an overlapping gene might constrain the sequence and proposed that translation of a second ORF might be initiated at the GUG codon at bases Ϫ41 to Ϫ39 and continue into the coding region+ However, the reading frame that contains this GUG has an in-frame stop codon (bases ϩ2 to ϩ4) that terminates it at the start of the main ORF+ This stop codon is present in all reported full-length core sequences; its presence reduces the likelihood that the GUG functions as the start codon for a protein that extends into the core-encoding region+ Smith and Simmonds (1997) concluded that the reduced frequency of synonymous substitutions "cannot be accounted for by additional coding restraints" (p+ 240)+ Recent studies indicate that the initial segment of the core-encoding region of the main HCV ORF contains features necessary for th...…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of protein synthesis requires the coordinated action of multiple translation components to mediate assembly of an 80S ribosome at the initiation codon of an mRNA (Merrick, 1992)+ First, a 43S complex is assembled from aminoacylated initiator tRNA, eukaryotic initiation factors (eIFs) 2 and 3, GTP and the small (40S) ribosomal subunit+ On the majority of mRNAs, eIF4F binds to the 59-terminal cap and promotes binding of the 43S complex to a cap-proximal region of the mRNA+ This complex requires eIFs 1 and 1A to locate the initiation codon by scanning in a 59-39 direction (Pestova et al+, 1998a)+ The resulting 48S complex is joined at the initiation codon by a large ribosomal subunit to form an 80S ribosome that is competent to begin protein synthesis (Pestova et al+, 2000)+ The accuracy of initiation codon selection is thought to be ensured by the base-by-base inspection of the 59 nontranslated region (59 NTR) by the scanning ribosome, which continues until base pairing is established between the initiation codon and the anticodon of initiator tRNA+ Translation initiation on various eukaryotic cellular and viral mRNAs is 59-end independent, and on a growing number of these mRNAs is known to occur following ribosomal attachment to an internal ribosomal entry site (IRES) (Johannes & Sarnow, 1998;Johannes et al+, 1999)+ IRESs are complex RNA structures that may contain multiple AUG triplets upstream of the initiation codon that are not recognized as start sites for translation (e+g+, Reynolds et al+, 1996;Pelletier et al+, 1988)+ Initiation codon selection therefore occurs by a mechanism unrelated to scanning+ One well-characterized group of IRESs includes hepatitis C virus (HCV) and classical swine fever virus (CSFV) (Tsukiyama-Kohara et al+,1992; Rijnbrand et al+, 1997)+ These IRESs are ;330 nt long (Fig+ 1), and comprise most of the 59 NTR (structural domains II and III, and a complex pseudoknot upstream of the initiation codon) and ;30 nt of the adjacent coding sequence (Reynolds et al+, 1995;Lemon & Honda, 1997;)+ They have related structures even though their sequences differ by ;55% (Wang et al+, 1995;Le et al+, 1998)+ These IRESs promote ribosomal attachment ("entry") at the initiation codon without prior scanning (Reynolds et al+, 1996;Rijnbrand et al+, 1996Rijnbrand et al+, , 1997)+…”
Section: Introductionmentioning
confidence: 99%